Synthesis, characterization and in vitro bioactivity of chitosan- hydroxyapatite composite doped with magnesium - Ismail Zainol (Tanjong Malim, 2019)
Synthesis, characterization and in vitro bioactivity of chitosan- hydroxyapatite composite doped with magnesium by Ismail Zainol